Scenarios: An Explorer's Guide (Shell International BV, 2008)
Exploring the Future The future is ‘terra incognita’: although we may be able to guess the outcome of events that lie close to us, as we pro ject beyond this we enter an unmapped zone full of uncertainty. Parado xically, the range of options this reveals can seem paralysing. No one can definitively map the future, but we can explore the possibilities in ways that are specifically intended to support decision-making. At Shell we use scenario building to help us wrestle with the developmen ts and behaviours that shape what the future may hold and prepare ours elves more effectively. We also believe it can inspire individuals and organisations to play a more active role in shaping a better future - for themselves, or even on a global scale. In this book, we use a met aphor of exploration and map-making to describe how we think about bui lding scenarios. Like a set of maps describing different aspects of a landscape, scenarios provide us with a range of perspectives on what m ight happen, helping us to navigate more successfully. Exploration - o f a territory or the future - involves both analytical thinking rooted in whatever facts are clear, and also informed intuition. This book d escribes the approach used to develop a set of global scenarios, ‘Peop le and Connections’ several years ago under the guidance of Ged Davis. Since then, scenarios guided by Albert Bressand have been published, and more recently Shell has published a summary of its Energy Scenario s, ‘Scramble’ and ‘Blueprints’, developed under the guidance of the cu rrent leadership. These have built on, and extended, our approach. Ind eed, Shell has been working with scenarios for almost 40 years, and we are still learning. Since the environment we live and work in is cons tantly changing, building scenarios demands continual innovation and c reativity.